Startup Sebagai Upaya Meningkatkan Jiwa entrepreneurship Di Kalangan Generasi Muda - Maiyana, Efmi; Yulastri, Asmar; Ganefri; Giatman; Effendi, Hansi; Muskhir, Mukhlidi (The Indonesian Journal of Computer Science, 2023)
Strategies used by startups to support young people in the business world, in the digital era and the ever-evolving global economy, business ethics have become more important than ever before. The high unemployment rate and the difficulty of finding a job are expected to be resolved by utilizing startup technology. Startups are the right place for the younger generation to develop and utilize the entrepreneurial spirit, with innovative, risky, and fast-moving characteristics. Various strategies can be used by startups to inspire and encourage young people to take calculated risks, be innovative and create their own business opportunities. Some successful startups that have inspired and prepared young people to become business owners. Through this analysis, the purpose of this article is to show how the younger generation can utilize the opportunities presented by startups to develop their own businesses, using qualitative descriptive methods creating a positive economic impact and bringing steady long-term change in the business world